The Influence of Motivation, Work Discipline, and Competence on Employee Performance at the Rizen Hotel Cisarua – Bogor - Ardiansyah; Samsuri; Yulianingsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his duties. Motivation, work discipline and competence will work well if the company pays attention to the things that employees want, which will have an impact on the company's desired targets.This research aims to determine the influence of motivation, work discipline and competence on the performance of employees at The Rizen Hotel Cisarua Bogor. The sample in this study amounted to 40 people. The results of the validity and reliability tests show that all question items are declared valid and reliable. Simultaneously motivation, work discipline and competence influence the performance of The Rizen Hotel employees. Partially, all independent variables influence employee performance.